Role of the Commission in supporting structural adjustment in ACP states (Office for Official Publications of the European Commission LuxembourgLU, 1992)
Explains the general concept of structural adjustment. Highlights the Commission's approach to the implementation of the structural adjustment facility, a major innovation of the Lomé IV Convention.
Located in the Office of the Secretary-General